2015
DOI: 10.1371/journal.pone.0141448
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs, miR-939, miR-595, miR-519d and miR-494, Identify Cirrhotic Patients with HCC

Abstract: The performance of circulating biomarkers for the diagnosis of hepatocellular carcinoma (HCC) is sub-optimal. In this study we tested circulating microRNAs as biomarkers for HCC in cirrhotic patients by performing a two stage study: a discovery phase conducted by microarray and a validation phase performed by qRT-PCR in an independent series of 118 patients. Beside miRNAs emerged from the discovery phase, miR-21, miR-221, miR-519d were also tested in the validation setting on the basis of literary and tissue f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 27 publications
3
111
2
1
Order By: Relevance
“…A whole microRNAome microarray analysis was applied to explore dysregulated expression of miRNAs in patients with cirrhosis, early, intermediate and advanced HCC. This study identified exosome-mediated dysregulation of circulatory miRNAs, miR-519d, miR-21, miR-221 and miR-1228 [17] . A significant reduction in miR-320a level was detected by miRNA sequencing of exosomes derived from cancer-associated stromal fibroblasts (CAFs) when compared to corresponding paracancer fibroblasts (PAFs) of 6 HCC patients [44] .…”
Section: Exosomal Rna Biomarkersmentioning
confidence: 87%
See 2 more Smart Citations
“…A whole microRNAome microarray analysis was applied to explore dysregulated expression of miRNAs in patients with cirrhosis, early, intermediate and advanced HCC. This study identified exosome-mediated dysregulation of circulatory miRNAs, miR-519d, miR-21, miR-221 and miR-1228 [17] . A significant reduction in miR-320a level was detected by miRNA sequencing of exosomes derived from cancer-associated stromal fibroblasts (CAFs) when compared to corresponding paracancer fibroblasts (PAFs) of 6 HCC patients [44] .…”
Section: Exosomal Rna Biomarkersmentioning
confidence: 87%
“…Circulating miRNAs, miR-939, miR-595, miR-519d and miR-494 could identify cirrhotic patients with HCC. Upon comparison of serum and tissue miR levels in 14 patients surgically treated for HCC, a correlation between circulating and tissue levels of miR-519d, miR-494 and miR-21 was found in HCC patients [17] . A whole microRNAome microarray analysis was applied to explore dysregulated expression of miRNAs in patients with cirrhosis, early, intermediate and advanced HCC.…”
Section: Exosomal Rna Biomarkersmentioning
confidence: 97%
See 1 more Smart Citation
“…The potential advantage over physical biopsies is dual, as the analysis is not limited to a single nodule, while the risk of dissemination is completely avoided. Exosomes specific to HCC have already been identified (25,26) and challenged on their efficacy in predicting recurrence after LT (27). The results are encouraging and the future of this technology is certainly bright.…”
Section: Hcc Biological Behaviormentioning
confidence: 99%
“…Distinguishing HCC are high circulating levels of miR-520b. In an in vivo study, high levels of miR-595 and miR-765 in plasma resulted in accurate diagnoses [15]. Also, a wide screen of miRNAs in blood plasma was done to measure accuracy of diagnoses for colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%